EXPOSITIVE TEXT COMPREHENSION. CLASSROOM STRATEGIES - Paradiso, Juan Carlos (Anales de Psicología / Annals of Psychology)
In this paper we explain a set of procedures which allows instruction on reading comprehension strategies. Proposed activities are deleting/selecting, identifying the main idea and title (macrorules), summarization, representing structures, outlining information in a diagram. They are easy to implementate and can all be accomplished working from a single paragraph. It is carefully chosen from an expositive prose text. The method implies problem–finding and problem–solving strategies in order to estimulate creativity as well as executive control processes. We think it presents important advantages with regard to direct instructional methods. Special attention is taken in order to allow individual reflexion and group discussion. The teacher role changes from a dispenser of knowledge to a mediator or a reflexive planner. This seems to be appropiate to elicitate prior knowledge, as well as motivate students and induce self activity. Besides, students seem to be more aware of their learning process.